KERAGAAN GENERASI KETIGA (M3) KEDELAI HASIL IRADIASI SINAR GAMMA PADA KONDISI OPTIMUM DAN KONDISI CEKAMAN KEKERINGAN - Hanafiah, Diana Sofia (Jurnal Online Pertanian Tropik, 2015)
The objective of this research was to obtain a genotype of selected putative mutant with good agronomic traits and high yielding on the optimum condition and its adaptability to drought stress in M3 generation. The study result showed that there were differences in the growth and production of each population as a result of irradiation in optimum conditions and drought stress conditions. The population as a result of irradiation at 150 Gy and 200 Gy had a higher mean value for the plant height trait, the number of productive branches, the number of productive nodes and the number of productive pods compared to irradiation population of 50 Gy, 100 Gy and the control population of Argomulyo at optimum conditions. The decrease in the growth and development happened to all the characters observed in the irradiation population in drought conditions compared to when grown in optimum conditions. The decrease can be seen in the characters of plant height, the number of pods and seed weight per plant. The growth and development of the population irradiation of 150 Gy and 200 Gy were more influenced by drought conditions compared to other irradiation populations. The selection in the optimum conditions produced 291 high yielding genotypes and the selection in drought conditions generated 202 genotypes and adapted to drought environments.